Impact of accounting information system quality on investment level and efficiency: An empirical analysis in Vietnam - Vo, Thi Thu Ha; Tran, Ngoc Hung; Hoang, Thanh Hien (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the influence of accounting information system (AIS) quality on the investment level and efficiency of publicly listed companies in Vietnam, employing SmartPLS software for data analysis. The quality of AIS is conceptualized through key dimensions, including reliability, timeliness, and relevance of financial data, which are essential for facilitating informed decision-making processes. The research utilizes structural equation modeling (SEM) to analyze data from economic reports and surveys conducted with key stakeholders in Vietnamese public companies. Results indicate that implementing high-quality Accounting Information Systems (AIS) significantly enhances investment efficiency by delivering accurate and timely information, facilitating improved capital allocation and risk assessment processes. Moreover, the study identifies that reliable AIS promotes transparency, bolsters investor confidence, and expands access to external financing. The findings underscore notable associations between AIS quality and compliance with regulatory standards, emphasizing its critical role in mitigating information asymmetry and reducing agency costs. Employing SmartPLS for analysis, the research provides compelling evidence of the mediating effects of AIS on organizational performance and investment outcomes. This study underscores the strategic imperative of developing robust AIS to optimize financial resource management and foster sustainable growth, particularly in emerging markets such as Vietnam.